Design Thinking: A Practical Method for Designing Stress Management Application Interfaces Using a Biomicroscopy Approach - Ernianti Hasibuan; Karin Rehulina; Evans Winanda Wirga (Asosiasi Dosen Muda Indonesia, 2025)
Academic stress is a significant challenge frequently faced by final-year students and can negatively impact their mental health and academic performance. This study aims to design a user interface for a stress management application using Design Thinking methods and a biomimicry approach, an approach that mimics natural patterns and principles to create more intuitive and effective design solutions. The research process involved in-depth interviews and usability testing with final-year students as the primary respondents. The results showed that the application of biomimicry principles in interface design can create an atmosphere resembling a natural environment that supports relaxation and provides a calming effect for users. Testing using the System Usability Scale (SUS) yielded an average score of 89.38, which falls into the Acceptable and Excellent categories based on the Adjective Rating scale. These findings indicate a very good level of acceptance and a satisfactory user experience. The implementation of the Design Thinking method, starting from the empathize stage to the prototype and test, combined with the biomimicry approach, successfully produced an interface design that is not only aesthetically pleasing and functional but also effective in helping students cope with academic stress.